Methods to determine the transcriptomes of trypanosomes in mixtures with mammalian cells: the effects of parasite purification and selective cDNA amplification - Mulindwa, Julius; Fadda, Abeer; Merce, Clementine; Matovu, Enoch; Enyaru, John; Clayton, Christine (PLoS neglected tropical diseases, 2014)
Patterns of gene expression in cultured Trypanosoma brucei bloodstream and procyclic forms have been extensively characterized, and some comparisons have been made with trypanosomes grown to high parasitaemias in laboratory rodents. We do not know, however, to what extent these transcriptomes resemble those in infected Tsetse flies - or in humans or cattle, where parasitaemias are substantially lower. For clinical and field samples it is difficult to characterize parasite gene expression because of the large excess of host cell RNA. We have here examined two potential solutions to this problem for bloodstream form trypanosomes, assaying transcriptomes by high throughput cDNA sequencing (RNASeq).
Gesehen am 23.09.2020